Malthusian Factors as Proximal Drivers of Human Population Crisis at Sub-Saharan Africa - Lima, Mauricio; Abades, Sebastián (Frontiers in Ecology and Evolution, 2015)
There is a growing interest and concern for understanding the interaction among human population growth and the sustainability of natural resources. In fact, many agrarian societies experienced an increasing frequency of wars, famines and epidemics during the periods of resource depletion. People from Sub-Saharan Africa (SSA) have suffered the demographic consequences of famines, civil wars and political instabilities during the last fifty years.. Almost half of the countries of Sub-Saharan Africa have undergone some form of demographic crisis over the past fifty years. Our analysis indicate that despite that environmental conditions were positively correlated with crop production across SSA, Malthusian factors correlated inversely with cultivation intensity, which in turn translated into a higher magnitude of depopulation suffered during the past fifty years. In this paper, we provide empirical evidence that population collapses in SSA during the last fifty years have been multifactorial, although more closely associated with ”Malthusian” factors as proximal drivers. Other proximal drivers such as economic indicators, political stability and environmental determinants did not explain as much variance as Malthusian forces, suggesting that explanations of collapse magnitude in SSA are embedded in a complex multi-causal chain, in which demographic factors may play a modulating role yet to be explored in more depth.